2017
DOI: 10.1128/jcm.00360-17
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Respiratory Syncytial Virus Outbreak on an Adult Stem Cell Transplant Unit by Use of Whole-Genome Sequencing

Abstract: A viral whole-genome sequencing (WGS) strategy, based on PCR amplification followed by next-generation sequencing, was used to investigate a nosocomial respiratory syncytial virus-B (RSV-B) outbreak in a hematology-oncology and stem cell transplant unit. RSV-B genomes from 16 patients and health care workers (HCWs) suspected to be involved in the outbreak were compared to RSV-B genomes that were acquired from outpatients during the same time period but epidemiologically unrelated to the outbreak. Phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In this study, we also observed that HRV/EV were associated with prolonged shedding and the most commonly found coinfections were PIV3 and HRV/EV. These results are consistent with previous findings that HRV/EV co-infection or different HRV species co-infection were associated with acute respiratory illness hospitalization and that prolonged viral shedding over the course of 30 days was more commonly associated with respiratory viruses [9,[20][21][22][23]. Because shedding of HRV can occur more than two weeks after infection [19], it could be interpreted that HRV was the most commonly found co-infection pathogen in this study.…”
Section: Quantitative Respiratory Virus Loadsupporting
confidence: 93%
“…In this study, we also observed that HRV/EV were associated with prolonged shedding and the most commonly found coinfections were PIV3 and HRV/EV. These results are consistent with previous findings that HRV/EV co-infection or different HRV species co-infection were associated with acute respiratory illness hospitalization and that prolonged viral shedding over the course of 30 days was more commonly associated with respiratory viruses [9,[20][21][22][23]. Because shedding of HRV can occur more than two weeks after infection [19], it could be interpreted that HRV was the most commonly found co-infection pathogen in this study.…”
Section: Quantitative Respiratory Virus Loadsupporting
confidence: 93%
“…Applying WGS and phylogenetic analysis, they excluded the possibility of a single source-transmission with a turnaround time of 24 hour. 240 Phylogenetic analysis applied to WGS revealed to be essential to discriminate nosocomial outbreak strains from other strains isolated in the same setting but not related to the outbreak event, as recently demonstrated by Zhu et al 241 during an epidemiological investigation performed on respiratory syncytial virus-B strains circulating within a unit of hematology and stem cell transplant. Authors compared the routine sequencing of glycoprotein (G) gene to the WGS and concluded that phylogenetic analysis applied to single gene sequence was not able to identify the cluster outbreak and that at this aim WGS was essential.…”
Section: Phylogenetic Analysis Of Whole-genome Sequencing For Viralmentioning
confidence: 85%
“…Authors compared the routine sequencing of glycoprotein (G) gene to the WGS and concluded that phylogenetic analysis applied to single gene sequence was not able to identify the cluster outbreak and that at this aim WGS was essential. 241 Recently phylogenetic analysis was used to investigate the measles outbreak of nosocomial origin occurred in Milan, Italy between March and August 2017. This study by phylogenetic inference demonstrated the occurrence of three nosocomial clusters within an emergency department initially notified as unrelated cases, suggesting the importance of measles vaccination especially for the healthcare workers.…”
Section: Phylogenetic Analysis Of Whole-genome Sequencing For Viralmentioning
confidence: 99%
“…Molecular characterization of RSV strains, for instance by whole genome sequencing [37] or characterization of RSV G-Protein [16,38], has been used to investigate nosocomial RSV outbreaks. We were able to collect and examine selected outbreak strains by G-Protein gene sequencing.…”
Section: Discussionmentioning
confidence: 99%